Stereoselective and Regioselective Pinacol‐Type Rearrangement of a Fused Bicyclic Oxetanol Scaffold. Issue 39 (18th October 2017) - Melis, Nicola; Luridiana, Alberto; Guillot, Régis; Secci, Francesco; Frongia, Angelo; Boddaert, Thomas; Aitken, David J.
Abstract : The Paternò‐Büchi reaction between benzaldehyde and trimethylsilyloxycyclopentene gave access to an unprecedented silyl ether derivative of 6‐oxabicyclo[3.2.0]heptan‐1‐ol. The bicyclic structure underwent selective reductive ring opening and acid‐catalyzed pinacol‐type rearrangement reactions with complete regioselectivity, accompanied by moderate to excellent mechanism‐dependent diastereoselectivity. Abstract : 6‐Oxabicyclo[3.2.0]heptan‐1‐ol derivatives, obtained by an efficient photochemical Paternò‐Büchi reaction, were used in a regio‐ and stereoselective Lewis acid catalyzed pinacol‐type rearrangement reaction.